Unravelling of Waste in a Touristic Area of Pangandaran from Neglecting Towards Embracing Informal Waste Management Practices, West Java, Indonesia - Bastiaan Schippers; Aninda Pratiwi (Humaniora, 2017)
Increased attention for sustainable waste management practices has in Indonesia resulted in legislation that seeks participation and self-regulation amongst people in urban and rural areas. However districts are trying to meet the expectations of the national government, implementing Westernized-recycling systems. We demonstrate that these top-down waste management practices as well as the current approach towardsscavenging systemsas being problematic and undesirable, will not lead to effective waste management. Using a holistic approach we explore the subjectivity of waste and alternating perceptions of these objects in both formal and informal waste management practices.Moreover this article considers the functioning of informal waste management systems to be dynamic and profitable. Within the context of a touristic area that can’t keep up with the increasing amount of solid waste, this article advocates a highly potential informal waste management practices that are systematically overlooked.